2020
DOI: 10.1177/2396987320923447
|View full text |Cite
|
Sign up to set email alerts
|

Effect of atrial fibrillation on endovascular thrombectomy for acute ischemic stroke. A meta-analysis of individual patient data from six randomised trials: Results from the HERMES collaboration

Abstract: Background Atrial fibrillation is an important risk factor for ischemic stroke, and is associated with an increased risk of poor outcome after ischemic stroke. Endovascular thrombectomy is safe and effective in acute ischemic stroke patients with large vessel occlusion of the anterior circulation. This meta-analysis aims to investigate whether there is an interaction between atrial fibrillation and treatment effect of endovascular thrombectomy, and secondarily whether atrial fibrillation is associated with wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 14 publications
1
41
0
Order By: Relevance
“…This is an important observation regarding the safety of MT in patients with LVO stroke related to AF. In line with the present multicenter experience, 25-50% of patients undergoing MT suffer from AF and as much as half of these have been using anticoagulation treatment in the period of stroke onset [12,20,22,23,25].…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This is an important observation regarding the safety of MT in patients with LVO stroke related to AF. In line with the present multicenter experience, 25-50% of patients undergoing MT suffer from AF and as much as half of these have been using anticoagulation treatment in the period of stroke onset [12,20,22,23,25].…”
Section: Discussionsupporting
confidence: 75%
“…AF is a common cause of LVO that necessitates endovascular treatment [9,[20][21][22]. MR CLEAN sub-analysis failed to confirm a significant effect of AF on MT outcomes [23,24]. Several separate retrospective studies found a negative effect of AF on the functional status of patients treated with endovascular therapy for stroke [12,15,16].…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent meta-analysis from the HERMES collaboration (Highly Effective Reperfusion Evaluated in Multiple Endovascular Stroke Trials) demonstrated no interaction between AF and functional outcomes after EVT, but found a trend towards a lower rate of symptomatic ICH in AIS patients with AF (3.4% in AF patients vs. 4.5% in non-AF patients), which might be related to the lower percentage of pre-treatment with IVT (76.3% in AF patients vs. 90.6% in non-AF patients). This is probably mainly due to the fact that patients with AF are more likely to taking oral anticoagulants, which is a contraindication for the administration of tPA [ 17 ]. Conversely, a post-hoc analysis of a multi-center head-to-head clinical trial revealed that AF was an independent risk factor for any ICH in AIS patients undergoing stent-retriever thrombectomy, which was partly attributable to the adjusted anticoagulation status and more retrieval attempts by mediation analyses [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent meta-analysis from the HERMES (Highly Effective Reperfusion Evaluated in Multiple Endovascular Stroke Trials) collaboration, which also includes perfusion imaging, comprising six randomised clinical trials evaluating outcome of sICH after ET alone or with intravenous rtPA administration, there was no difference in the rate of sICH in patients with AF (3.4%) than without AF (4.5%). 15 They also did not find a difference in outcome between patients who had large vessel occlusion stroke with and without AF. 15 This result is further confirmed by another study performed using the multicentre Stroke Thrombectomy and Aneurysm Registry, which concluded that the presence of premorbid AF in patients who achieved good recanalisation post ET did not impact sICH rates (aOR 0.69, 95% CI 0.43 to 1.12).…”
Section: Resultsmentioning
confidence: 92%
“… 15 They also did not find a difference in outcome between patients who had large vessel occlusion stroke with and without AF. 15 This result is further confirmed by another study performed using the multicentre Stroke Thrombectomy and Aneurysm Registry, which concluded that the presence of premorbid AF in patients who achieved good recanalisation post ET did not impact sICH rates (aOR 0.69, 95% CI 0.43 to 1.12). 16 A large 2015 multicentre retrospective analysis searched for risk factors for ICH after ET and found that AF was associated with a higher risk of ICH, but this result did not persist after adjusting for vascular risk factors.…”
Section: Resultsmentioning
confidence: 92%